Pituitary dwarfism in a Poodle dog: clinical and laboratory findings - Cruz, Kariny S. (2020)
This paper aimed to evaluate the clinical and laboratory findings of a case of pituitary dwarfism in a 4-month-old female Poodle dog. The clinical signs observed were a reduced body size, soft and woolly coat, retention of the sub-coat, absence of primary hairs, scaling of the skin of the head region and deciduous teeth. Hormonal analyses indicated values of 0.5 ng/ml for growth hormone (GH), 0.44 ng/ml for total T3 and 1.44 ng/dl for free T4. GH levels were below normal, thus indicating a pituitary dwarfism.